2004
DOI: 10.1023/b:biry.0000029851.96180.92
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Codon Usage and Irregularities of Rare Codon Distribution in Genes for Expression of BspLU11III Methyltransferases

Abstract: Genes of adenine-specific DNA-methyltransferase M.BspLU11IIIa and cytosine-specific DNA-methyltransferase M.BspLU11IIIb of the type IIG BspLU11III restriction-modification system from the thermophilic strain Bacillus sp. LU11 were expressed in E. coli. They contain a large number of codons that are rare in E. coli and are characterized by equal values of codon adaptation index (CAI) and expression level measure (E(g)). Rare codons are either diffused (M.BspLU11IIIa) or located in clusters (M.BspLU11IIIb). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In particular, we tested the role of rare arginine cluster near the start codon of REase and found its potential regulatory function in protein synthesis, R-M system maintenance and impact on the host cell fitness. We found that the cluster of rare arginine codon alone negatively affects the REase synthesis, as the delivery of tRNAs for the rare arginine codons highly increased its expression, in accord with other reports related to production of heterologous proteins 72,73 . Indeed, the tRNAs’ availability seems to be the limiting factor for the protein synthesis, when the rare codon cluster is located close to translational start of the gene.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, we tested the role of rare arginine cluster near the start codon of REase and found its potential regulatory function in protein synthesis, R-M system maintenance and impact on the host cell fitness. We found that the cluster of rare arginine codon alone negatively affects the REase synthesis, as the delivery of tRNAs for the rare arginine codons highly increased its expression, in accord with other reports related to production of heterologous proteins 72,73 . Indeed, the tRNAs’ availability seems to be the limiting factor for the protein synthesis, when the rare codon cluster is located close to translational start of the gene.…”
Section: Discussionsupporting
confidence: 91%
“…Codon analysis of the recovered sequences revealed that nearly all the recovered genes contained a higher number of rare E. coli codons than the native nfsA or nfsB genes ( Table 1), which suggested that sub-optimal codon use might be impairing translation and thereby limiting their perceived activity in this host. To alleviate this issue, we co­transformed these strains with pRARE (a plasmid derived from the ROSETTA strain that supplements E. coli cells with rare tRNAs; Kirienko et al, 2004) and evaluated its effect on levels of enzyme expression ( Figure 4B ) and metronidazole IC 50 ( Table 1). Improvements in each parameter were observed for the majority of variants, with the sensitivity to metronidazole of E. coli cells bearing five different nitroreductases (NfsB2, NfsB3, SagBl, TdsD2, and TdsD3) enhanced by over 3-fold ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial cultures were grown and assessed in Lysogeny Broth (LB) amended with antibiotics as appropriate for plasmid maintenance (100 µg.mL -1 ampicillin for pUCX or pRSETB, 20 µg.mL -1 gentamycin for pUCXMG, and/or 30 µg.mL -1 chloramphenicol for pRARE). Plasmid pUCX was previously generated in house (Prosser et al, 2013; Addgene plasmid #60681), pRSETB bearing a soil eDNA library was kindly provided by Nadia Parachin and Marie Gorwa-Grauslund (Parachin and Gorwa-Grauslund, 2011), pRARE was as described by Kirienko et al (2004), and pUCXMG was created for this study as described below.…”
Section: Star Methodsmentioning
confidence: 99%
“…JCat tool was used for the same purpose and a 1302 long cDNA sequence of the vaccine construct was generated for E. coli K-12 strain [46] . For effective expression of a protein within E. coli, the codon adaptation index (CAI) value should be > 0.8 while the GC content must be around 30-70% [47] . Our construct shows a CAI of 1.0 and GC content of 53.76%, this reflects proficient protein expression in the bacterial cell system.…”
Section: Resultsmentioning
confidence: 99%